There can be no answer because the question contains an expression, not an equation or inequality.
x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2
x(x4+x3+x2+x+1)
(X) x (4) x (8) x (12) = 384 X
no...why would it.... it equals 2x+9
= 18x + 13
25x2y
Oh, dude, that's like a lot of x's and t's and some random letters thrown in there. So, technically, if you add all the x's, you get 7x, add all the t's, you get 3t, and the random letters are just there for decoration, I guess. So, the sum of x plus x plus x plus x plus x plus x plus x plus t plus t plus t plus jjakw is 7x + 3t + jjakw.
4X
It is 123.99
x=27
x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2
x+x+1+x+2+x+25=845 4x+28=845 4x=817 x=204.25
X= 5
x(x4+x3+x2+x+1)
(X) x (4) x (8) x (12) = 384 X
yes cause like when u do x plus x plus x , its like 1 plus 1 plus 1 so its 3x just like 3
no...why would it.... it equals 2x+9